OIL SPILL RESPONSE PREPAREDNESS MODEL THROUGH COMMUNITY PARTICIPATION IN TELUK PENYU BEACH, CILACAP REGENCY - Soesilo, Tri Edhi Budhi; Rezki, Chiquita Tri; Sulthonuddin, Ihya (Journal of Environmental Science and Sustainable Development, 2019)
In Indonesia, oil spill incidents often occur; thus, it has become a matter of national concern. Cilacap Regency is one of the regions in Indonesia that is prone to oil spills, with a history of frequent oil spill incidents during 2000–2018. Oil spill response preparedness needs the integrated effort between government and communities to minimize the environmental impacts of oil spills. A problem usually encountered is the lack of integration of community participation in the oil spill contingency plan because of the limited knowledge of the community regarding oil spill response preparedness. This study aimed to build an oil spill response preparedness model through community participation in Teluk Penyu Beach, Cilacap Regency. This study used the system dynamics modeling method. Results showed that the oil spill volumes in the waters (decay behavior) and on the beach (goalseeking behavior) rapidly decreased after 240 h (10 days). In conclusion, oil spill response preparedness needs the integration between company and community participation by increasing knowledge through community involvement in a combination of oil spill response exercises.